Outsourcing Non-Core Services in Healthcare: A Cost-Benefit Analysis - Karakolias , Stefanos (International Journal of Scientific Research and Management (IJSRM), 2024)
Outsourcing non-core services in healthcare, such as housekeeping, IT support, catering, and security, has emerged as a popular strategy for healthcare organizations looking to reduce costs and focus on patient care. This paper presents a comprehensive cost-benefit analysis of outsourcing these services, considering both financial and operational implications. Through a combination of quantitative analysis and qualitative insights from healthcare administrators, the study explores how outsourcing affects cost savings, operational efficiency, and overall service quality.The findings indicate that outsourcing non-core services can lead to significant cost reductions—ranging from 7% to 28% depending on the service—while also enhancing operational efficiency. In particular, services such as housekeeping and IT support benefit from outsourcing due to the specialized expertise of third-party providers. Outsourced services not only reduce internal operational burdens but also contribute to a more streamlined allocation of resources toward core healthcare functions, including patient care.However, the analysis also highlights several risks, such as loss of control over service quality and concerns related to data security, particularly when IT services are outsourced. These challenges can potentially affect the reliability of healthcare operations if not properly managed. The study suggests that healthcare organizations must implement strict service-level agreements (SLAs) and performance monitoring mechanisms to mitigate these risks and ensure continuity of high-quality service delivery.